Same-Day Compared With Overnight Cervical Preparation Before Dilation and Evacuation Between 16 and 19 6/7 Weeks of Gestation: A Randomized Controlled Trial. Issue 6 (2nd June 2022) - Kim, Chi-Son; Dragoman, Monica; Porsch, Lauren; Markowitz, Jess; Lunde, Britt; Stoffels, Guillaume; Dayananda, Ila
Abstract : Same-day cervical preparation with osmotic dilators plus buccal misoprostol before dilation and evacuation is feasible. Abstract : We performed a double-blind, placebo-controlled, randomized noninferiority trial to compare same-day osmotic dilators plus misoprostol with overnight osmotic dilators alone for cervical preparation before dilation and evacuation (D&E) between 16 0/7 and 19 6/7 weeks of gestation. The primary outcome was procedure time. The study was halted early owing to poor accrual. However, the median procedure time was 5.7 minutes in the same-day group compared with 4.2 minutes in the overnight group. The median absolute difference in procedure time was 1.5 minutes, which corresponded to a 35% increase in procedure time (relative difference 35%, one-sided 95% CI −Inf to 52%). Same-day cervical preparation with osmotic dilators plus buccal misoprostol before D&E may be a timely option. Clinical Trial Registration: ClinicalTrials.gov, NCT03002441.